Improvement of the spectroscopic parameters of the air- and self-broadened N2O and CO lines for the HITRAN2020 database applications. (September 2021) - Hashemi, Robab; Gordon, Iouli E.; Adkins, Erin M.; Hodges, Joseph T.; Long, David A.; Birk, Manfred; Loos, Joep; Boone, Chris D.; Fleisher, Adam J.; Predoi-Cross, Adriana; Rothman, Laurence S.
Abstract: This paper outlines the major updates of the line-shape parameters that were performed for the nitrous oxide (N 2 O) and carbon monoxide (CO) molecules listed in the HITRAN2020 database. We reviewed the collected measurements for the air- and self-broadened N 2 O and CO spectra to determine proper values for the spectroscopic parameters. Careful comparisons of broadening parameters using the Voigt and speed-dependent Voigt line-shape profiles were performed among various published results for both N 2 O and CO. Selected data allowed for developing semi-empirical models, which were used to extrapolate/interpolate existing data to update broadening parameters of all the lines of these molecules in the HITRAN database. In addition to the line broadening parameters (and their temperature dependences), the pressure shift values were revised for N 2 O and CO broadened by air and self for all the bands. The air and self speed-dependence of the broadening parameter for these two molecules were added for every transition as well. Furthermore, we determined the first-order line-mixing parameters using the Exponential Power Gap (EPG) scaling law. These new parameters are now available at HITRAN o n l i n e .